Femtosecond laser ablation of dielectric layers for high-efficiency silicon wafer solar cells. (April 2018) - Yacob Ali, Jaffar Moideen; Shanmugam, Vinodh; Lim, Bianca; Aberle, Armin G.; Mueller, Thomas
Highlights: Laser ablation of dielectric layers with minimal damage to the underlying silicon was successfully performed using a femtosecond laser source. The laser damage induced in the gentle regime can be etched off in a short time (5 s). In the strong ablation regime, the laser damage cannot be completely removed even during 15 min of KOH etching, indicating the presence of bulk damage. Hence, gentle laser ablation at very high repetition rate (2 MHz) is highly suitable for industrial mass production of high efficiency silicon wafer solar cells. Abstract: Laser ablation of dielectric layers to form local contacts while inducing negligible electronic damage to the underlying substrate is crucial for high-efficiency silicon solar cell fabrication. In this work, ablation of dielectric layers such as SiNX, AlOX /SiNX stacks and thermal SiO2 /PECVD SiNX stacks is performed using laser pulses with a pulse duration of 480 fs and a wavelength of 515 nm. At this wavelength the femtosecond (fs) laser pulses are typically absorbed in the underlying silicon (indirect ablation), causing defects. However, by precisely determining the single pulse ablation properties such as threshold fluence, spot radius (r) and energy penetration depth (z0 ) and by optimising the line ablation process, it is possible to ablate the dielectrics with little to no damage to the substrate. Upon analysing r and z0, two distinct ablation regimes, 'gentle' and 'strong', are identified. Etch-back processing and photoluminescence analysis shows that the strong ablation regime needs more than 15 min of damage etching, corresponding to an etch depth of about 18 µm and thus indicating bulk damage. However, in the gentle regime the defects can be etched off in less than 5 s, indicating that the damage is confined to less than ∼100 nm from the wafer surface, which agrees with the z0 determined for the gentle regime. Hence, gentle fs laser ablation is highly suitable for industrial mass production of ablation intensive and high-efficiency silicon wafer solar cells.